Prevalence of undiagnosed, preventable visual impairment in children with intellectual disability in special needs schools in Western Saudi Arab - Lina Hassan Raffa; Abdulrahman Zaid Al-Shamrani; Firas Mohamed Madani; Ali Saad AlQarni; Kareem Fawzi Allinjawi; Abdulrahman Khalid Fagih; Nizar Alhibshi (Saudi Journal for Health Sciences, 2021)
Background: Visual disorders have been reported to be higher among children with intellectual disability (ID) than among their peers without special needs; however, prevalence data on visual problems in children in Saudi Arabia are scarce. Aims: The aim of this study is to report the prevalence and causes of undiagnosed, correctable visual impairment in children with ID. Materials and Methods: A cross-sectional study of students enrolled in special educational needs schools in the western region of Saudi Arabia in April 2018. Teller visual acuity (VA) assessment and refractive errors were noted. Participants with mild to profound ID underwent detailed ophthalmologic examinations, including cycloplegic refraction, full orthoptic workup, biomicroscopy, and funduscopy. Results: A total of 61 students participated in this study. Ocular findings in decreasing prevalence were as follows: Subnormal VA (n = 41, 67.2%), refractive errors (n = 31, 51.7%), fundus anomalies (n = 13, 22%), significant strabismus (n = 9, 14.8%), abnormal head posture (n = 8, 13.3%), nystagmus (n = 3, 4.9%), anterior segment abnormality (n = 3, 4.9%), and extraocular motility abnormality (n = 2, 3.3%). Astigmatism was found in 22 cases (36.7%), followed by hyperopia (n = 13, 21.7%), myopia (n = 10, 16.7%), and anisometropia (n = 5, 8.3%). Students with syndromic ID had significantly more moderate-to-severe subnormal VA (P < 0.001) and myopic shift on cycloplegic refraction (P = 0.014 right eyes and P = 0.004 left eyes) than those with nonsyndromic ID. Conclusions: A considerable proportion of ID children have significant visual disorders. This emphasizes the need for adequate diagnostic and therapeutic national eye care services for children with ID.